Features of the EDELIVERY implementation in the context of electronic trust services. The experience of the Euro-Union - Brochevan, E.V.; Potii, A.V. (Radiotekhnika, 2018)
The components of Connecting Europe Facility and the eDelivery service are considered. The organizational and architectural features of the implementation of the registered documents delivery and its functions are analyzed. Describes The process of deploying the infrastructure for the service and its design is described. The experience of using the service in the EU countries is considered.